Study on Environment Awareness and Culture Sustainability in India - Dr. Sanjay Shahi (International Journal of Engineering and Management Research, 2018)
Instead of following the cycle of over-exploitation of natural resources for development and then looking for ways to reduce its environmental impacts, India as a country can find the solutions to sustainable development by focusing on our roots of culture and lifestyle and moving forward on the path of development. There are various ways to reduce our carbon footprints simply by changing our current consumption and modern lifestyles and returning to our traditional ways of existence. Ancient Indian techniques of environmental conservation can help us better manage our natural resources now. For development to be complete, it must include the well-being and harmony of all living things on the planet as a whole. India's culture and way of life provide a variety of strategies to promote sustainable development. This study will examine several traditional Indian practises for environmental conservation and their relevance and practicality in today's era of environmental degradation.